How Tech Hubs are Helping to Drive Economic Growth in Africa - Kelly, Tim; Firestone, Rachel (World Bank, Washington, DC, 2016)
Digital technologies have spread rapidly. Digital dividends—the broader development benefits from using these technologies—have not. Digital technologies to benefit everyone everywhere requires improving the “analog” complements to digital investments—by strengthening regulations that ensure competition among businesses, by adapting workers’ skills to the demands of the new economy, and by ensuring that institutions are accountable. Inclusion, efficiency, innovation are the main mechanisms for the internet to promote development. How can these mechanisms be leveraged to promote Africa’s development? The paper tracks some 117 Tech Hubs across Africa, many of which have been created in the last few years. The paper looks at the patterns of origin by which Tech Hubs are created, why they have a high failure rate, and what makes for success.